Strategi Pendistribusian Zakat Melalui Program Tanah Datar Sehat di BAZNAS Kabupaten Tanah Datar - Novi Rahma Dani (ZAWA: Management of Zakat and Waqf Journal, 2022)
BAZNAS Tanah Datar District has five programs, one of the most important programs is Tanah Datar Sehat. There are several problems that trigger this research, namely the distribution of zakat for the Tanah Datar Sehat program which exceeds and is less than RKAT funds and the number of mustahik for the Tanah Datar Sehat program always increases every year. Therefore the authors wish to conduct research on the zakat distribution strategy carried out by BAZNAS Tanah Datar Regency for the health program. The type of research that the authors use is (field research) field research with qualitative descriptive methods. Data collection techniques that the authors do are interviews and documentation. The results of the research that the authors found regarding the strategy carried out by BAZNAS for Tanah Datar Regency, namely regarding the zakat distribution program BAZNAS for Tanah Datar Regency has five programs: Tanah Datar Smart, Tanah Datar Prosperous, Tanah Datar Cares, Tanah Datar Madani and Tanah Datar Sehat. Especially about the Healthy Flat Land program. The strategy carried out by BAZNAS of Tanah Datar Regency in distributing zakat is by determining goals and targets, formulating strategies, determining the resources needed. Regarding the obstacles faced by BAZNAS of Tanah Datar Regency in distributing zakat in the Tanah Datar Sehat program, namely due to weather factors, lack of completeness of mustahiq administration, delays in reporting survey results by amil. When the funds distributed exceed or fall short of the Annual Budget Work Plan (RKAT), BAZNAS carries out a cross system, namely the excess funds are transferred to the following year. While the funds were lacking that year, the funds were taken from other program funds that were not realized.